2009
DOI: 10.1521/aeap.2009.21.5.474
|View full text |Cite
|
Sign up to set email alerts
|

HIV Seroprevalence in a Sample of Tanzanian Intravenous Drug Users

Abstract: Injection drug use has recently emerged in sub-Saharan Africa. The purpose of this study was to assess the factors associated with increased risk of testing HIV-positive in a sample of injection drug users (IDUs) in Dar es Salaam, Tanzania. Participants were recruited by a trained outreach worker or were referred by IDUs who had completed the study. Blood specimens and self-reported socioeconomic and behavioral data were collected from 315 male and 219 female IDUs. Data were analyzed using univariate odds rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 28 publications
2
55
1
Order By: Relevance
“…Since 2003, the majority of PWID in Dar es Salaam reported injecting three times per day [2, 5, 6], with 41% of all users sharing needles in the past 30 days [6]. In addition, 28% of PWID reported reusing used rinse water [1], which is not effective in preventing HIV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2003, the majority of PWID in Dar es Salaam reported injecting three times per day [2, 5, 6], with 41% of all users sharing needles in the past 30 days [6]. In addition, 28% of PWID reported reusing used rinse water [1], which is not effective in preventing HIV.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to sexual risk behavior, only 42% of PWID reported using condoms during sex in the last 30 days [7]. Studies conducted between 2003 and 2007 estimated an HIV prevalence of 42% among PWID [6, 8], compared to an estimated prevalence of 9% in the general population [9]. Subsequent studies conducted between 2009 and 2010 found an HIV prevalence among younger PWID of approximately 31% and 35%, respectively [5, 10].…”
Section: Introductionmentioning
confidence: 99%
“…An estimated 42% of people who inject drugs (PWID) in Dar es Salaam have HIV. 3 These HIV-infected injectors have a more than 20- to 37-fold risk of TB compared to non-HIV-infected persons. 4,5 As of 2009, Tanzania ranked fifteenth among the 22 high TB burden countries.…”
mentioning
confidence: 99%
“…With financial support from the U.S. National Institutes Drug Abuse, researchers conducted numerous studies of drug use practices in Dar es Salaam and on the island of Zanzibar between 2003 and 2007 to demonstrate the links between heroin injection and HIV transmission (Dahoma, et al, 2006; McCurdy, et al, 2005; 2006; Timpson, et al, 2006; Williams, et al, 2007). Results from these surveys indicated that the prevalence of HIV infection among those who injected heroin was between 26% and 42% in Dar es Salaam, compared to an overall national prevalence of 9% (Williams, et al, 2009). …”
Section: Harm Reduction In Tanzania: a Story Of Self-organization Andmentioning
confidence: 99%